2005
DOI: 10.1055/s-2005-837601
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Pecularities of the Submucous Plexus in the Human Anorectum - Consequences for Histopathologic Evaluation of Rectal Biopsies

Abstract: Chronic colorectal motility disorders are commonly encountered in the pediatric population. While most cases can be managed successfully by conservative therapy, a subgroup of patients suffers from severe constipation and requires further diagnostic procedures to identify the underlying pathologies, such as aganglionosis, hypoganglionosis or intestinal neuronal dysplasia (IND). The present study provides reference data about the quantitative distribution of nerve cells and ganglia within the submucosal plexus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…A reliable diagnosis using a hematoxylin-eosin morphological examination of mucosal biopsies is very difficult because the submucosal ganglia are very small (3 -5 cells per ganglion) and spread inside the Meissner's plexus. These anatomical findings explain the low reliability and false positive results of classical histomorphological (H&E) studies of suction rectal biopsies in suspected HSCR cases [46,47,71]. In 1972, Meier-Ruge [49] started to investigate the acetylcholinesterase (AChE) enzyme-histochemical reaction and revealed a markedly increased AChE activity in a large number of cholinergic nerve fibers and thick nerve trunks present in HSCR.…”
Section: The Era Of Histochemistrymentioning
confidence: 99%
“…A reliable diagnosis using a hematoxylin-eosin morphological examination of mucosal biopsies is very difficult because the submucosal ganglia are very small (3 -5 cells per ganglion) and spread inside the Meissner's plexus. These anatomical findings explain the low reliability and false positive results of classical histomorphological (H&E) studies of suction rectal biopsies in suspected HSCR cases [46,47,71]. In 1972, Meier-Ruge [49] started to investigate the acetylcholinesterase (AChE) enzyme-histochemical reaction and revealed a markedly increased AChE activity in a large number of cholinergic nerve fibers and thick nerve trunks present in HSCR.…”
Section: The Era Of Histochemistrymentioning
confidence: 99%
“…This zone reaches different levels above the dentate line: 10-25 mm for submucosal, while only 5 mm for the myenteric plexus. [28][29][30] As the near-fullthickness rectal biopsies also contain the myenteric plexus, they can be taken closer to the dentate line, and can therefore diagnose a very short segment HD more reliably than suction biopsies. [28][29][30] Furthermore, 9 to 17% suction biopsies are reported to be inadequate by most large series, principally due to insufficiently included submucosa, which increases the risk for false diagnosis and the necessity to rebiopsy.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] As the near-fullthickness rectal biopsies also contain the myenteric plexus, they can be taken closer to the dentate line, and can therefore diagnose a very short segment HD more reliably than suction biopsies. [28][29][30] Furthermore, 9 to 17% suction biopsies are reported to be inadequate by most large series, principally due to insufficiently included submucosa, which increases the risk for false diagnosis and the necessity to rebiopsy. 24,28,31,32 A further disadvantage of suction biopsies is the limited size of obtainable specimen and the difficulty of accurate positioning of the suction biopsy device, especially in a moving child.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Iwase et al [60] reported a decrease in the number of myenteric neurons in colonic diverticular disease. This is highlighted in the study by Tafazzoli et al [61] who demonstrated segment-specific quantitative differences of the anorectal submucous plexus which must be taken into consideration for the histopathologic evaluation of rectal biopsies. This is highlighted in the study by Tafazzoli et al [61] who demonstrated segment-specific quantitative differences of the anorectal submucous plexus which must be taken into consideration for the histopathologic evaluation of rectal biopsies.…”
Section: Plasticity In the Enteric Innervationmentioning
confidence: 99%